Penyusunan Instrumen Tes Bagi Guru Matematika Berbasis Problem Solving dan Literasi Numerasi - Rohantizani Rohantizani; Nuraina Nuraina; Jumadi Jumadi; Nur Fadhilah; Nurjannah Nurjannah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
This community service activity was motivated by the limited competence of high school mathematics teachers in developing test instruments as a strategy for mathematics learning based on problem solving and numerical literacy. In addition, teachers’ creativity in designing learning tools—particularly test instruments aligned with teaching modules and student worksheets (LKPD) based on problem solving and numerical literacy—remains low. Therefore, this training program was designed to enhance teachers’ competence and creativity in developing test instruments as part of effective learning strategies, especially those integrated with problem solving and numerical literacy-oriented teaching modules and LKPD. The methods employed in this program include lectures, interactive discussions, and hands-on training. The lecture method was used to deliver theoretical concepts related to test instruments that align with problem solving and numerical literacy-based modules and LKPD. The training method involved participants directly in the process of designing and developing learning strategies. Meanwhile, the dialogic method was implemented to address challenges encountered by participants during the training sessions. The target participants of this program were high school mathematics teachers in North Aceh. The training provided significant benefits, particularly in improving teachers’ competence and creativity in developing effective mathematics learning tools.